Effect of nonsurgical periodontal therapy on interleukin-34 levels in periodontal health and disease - C N Guruprasad; A R Pradeep (Wolters Kluwer Medknow Publications, 2018)
Background: Interleukin-34 (IL-34) is a recently identified alternative ligand for colony-stimulating factor-1 receptor plays an important role in osteoclastogenesis. The aim of this study was to evaluate the IL-34 levels in gingival crevicular fluid (GCF) and plasma in subjects with chronic periodontitis and to evaluate the effect of nonsurgical periodontal therapy on the GCF and plasma IL-34 levels. Materials and Methods: Thirty individuals (age range: 30-56 years) were selected and divided into groups based on the gingival index, probing pocket depth, clinical attachment level, and radiologic parameters (bone loss): Group I (15 individuals with healthy periodontium), Group II (15 individuals with chronic generalized periodontitis) while Group II patients after 8 weeks of the treatment (scaling and root planning) constituted Group III. GCF samples and plasma samples were collected to estimate the levels of IL-34 using enzyme-linked immunosorbent assay kit. Results: The mean IL-34 concentration in GCF and plasma was highest for Group II compared to Group I and decreased after nonsurgical periodontal therapy in chronic generalized periodontitis group. The difference between them was statistically significant (P < 0.05). Conclusion: IL-34 can be considered as an "inflammatory marker" of periodontal disease and can be explored in the future as a potential therapeutic target in the treatment of periodontal disease.